2014
DOI: 10.4102/jsava.v85i1.1002
|View full text |Cite
|
Sign up to set email alerts
|

Caudal epidural analgesia using lidocaine alone or in combination with ketamine in dromedary camels (<i>Camelus dromedarius</i>)

Abstract: This study was performed to investigate the analgesic effect of lidocaine and a combination of lidocaine and ketamine following epidural administration in dromedary camels. Ten 12-18-month-old camels were randomly divided into two equal groups. In group L, the animals received 2% lidocaine (0.22 mg/kg) and in group LK the animals received a mixture of 10% ketamine (1 mg/kg) and 2% lidocaine (0.22 mg/kg) administered into the first intercoccygeal (Co1-Co2) epidural space while standing. Onset time and duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 19 publications
3
30
0
Order By: Relevance
“…Administration of lidocaine with ketamine produced longer duration of analgesia in dogs and cats than lidocine alone (De Rossi et al, 2009 andDe Rossi et al, 2011). Azari et al (2014) reported that, no significant differences in onset and intensity of analgesia in camels between lidocaine and lidocaine /ketamine combination. However Moulvi et al (2011) reported that, combination of ketamine with lignocaine resulted in more rapid and intense analgesia than lignocaine alone in calves.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Administration of lidocaine with ketamine produced longer duration of analgesia in dogs and cats than lidocine alone (De Rossi et al, 2009 andDe Rossi et al, 2011). Azari et al (2014) reported that, no significant differences in onset and intensity of analgesia in camels between lidocaine and lidocaine /ketamine combination. However Moulvi et al (2011) reported that, combination of ketamine with lignocaine resulted in more rapid and intense analgesia than lignocaine alone in calves.…”
Section: Discussionmentioning
confidence: 99%
“…Sedation onset and duration were also recorded. It was graded on 1 to 4 scores for each dose according to Azari et al (2014). (Table, 1).…”
Section: Clinical Assessementmentioning
confidence: 99%
See 2 more Smart Citations
“…Biochemical Analysis: Glucose Estimation: Fasting blood glucose level was measured on 4 th day of treatment by PCPA and STZ in animals by using glucometer from the ventral side of the tail, 1cm away from the cloacae. 2 % lidocain was used for every pricking to reduce the pain 18 .…”
Section: Drug's Informationmentioning
confidence: 99%